Sacred landscapes in Asia : shared traditions, multiple histories - Himanshu Prabha Ray(Editor) (Manohar Publishers & Distributors : Distributed in South Asia by Foundation Books, 2007)
Contributed articles emanating from two conferences held at India International Centre, New Delhi on April 26-27, 2004, and Indian Institute of Advanced Study, Shimla on October 25-27, 2004; part of IIC-Asia Project.